Almost Entropy Convergence for Fuzzy Sequence Spaces - Zarife Zararsız (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this paper, weintroduce a new type convergence called almost entropy convergence forsequences of fuzzy numbers. In addition this, we show that almost entropyconvergence can be defined as the intersection of convergence field of Cesàro matrix. Besides,we generalize this idea to any matrix T. By this way,we present the definition of T- entropyconvergence. After, the set of all almost entropy convergent and null almostentropy convergent sequences of fuzzy sets are defined. In addition this, we give some theorems, forexample, we show that the sets E_f and E_f_0are complete metric spaces and give theinclusion relations between the spaces E_c, E_fand E_c, and proofs on this notion.